Students’ Perceptions of AI Use in Supporting Critical Thinking: A Small-Scale Survey of English Education Students - Eka Apriani; Muthmainnah; Stefhanie Putri Cusa Gempar; Hengki Kris Sanjaya; Mona Refaat Taman; Dadan Supardan (Language and Education Journal, 2026)
When Artificial Intelligence (AI) was incorporated into higher education, there was a major change. However, AI's influence on critical thinking remains an important issue for teachers. This study uses a quantitative survey design to explore the role of AI in developing critical thinking skills. The sample for this study comprised 10 fifth-semester students from the English Language Studies Study Program at IAIN Curup who followed the STEM education path. Data were collected using a structured questionnaire instrument with a 5-point Likert scale, validated to measure the frequency of AI use and critical thinking indicators. The findings show diversity in students' perceptions of AI's effectiveness in supporting their cognitive processes. From the descriptive findings, it has been revealed that 30 percent of the respondents strongly agreed and another 20 percent agreed with the proposition stating that the use of artificial intelligence increases efficiency in learning and processing information. However, there are also plenty of doubts: 30 percent of respondents were unsure about this issue, while 20 percent disagreed. This suggests a risk of dependence that may interfere with critical thinking and rational judgment when technology is used improperly. It is important to note that the results of the current study cannot be generalized due to the limited sample size.